Consolidation of The Issue of Maslahah Mursalah Regarding Peusijuek Towards Marriage Culture of Aceh Society - Nauratul Islami; M. Khoirul Hadi al-Asy ari; Muhammad Asyraf (Faculty Sharia of State Islamic University (UIN) Palangka Raya, 2025)
Aceh is an area full of culture and local wisdom. One tradition that is still preserved and practiced is Peusijuek. The Peusijuek procession naturally becomes a culture that must be preserved because it contains very philosophical religious values. Peusijuek is a culture that has become part of Islam. This is seen from the three elements of Peusijuek, namely the perpetrator of Peusijuek, the moment, and the prayer that is read. One of Peusijuek's moments is at a wedding. The aim of this research is to critically examine Peusijuek using the mashlahah murlah method. Where mashlahah murlah is a method of establishing law that is very effective in providing solutions. This research is a literature review, where the data sources are obtained from various books, scientific articles, journals, and so on. The author uses a qualitative approach that is descriptive and leads to analysis. The results of this research show that the peusijuek procession in Acehnese society is not only considered a tradition, but is also considered part of religious rituals and a form of women's involvement in traditions in the realm of tradition. This is seen from the strong religious philosophical values ​​in the peusijuek procession. The concept of maslahah murrasa refers to the principle that Islam aims for the benefit of the people, and makes society's life better and more harmonious.